THE RELIABILITY OF ESSAY TEST - Eriza - - (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2010)
Besides validity and accuracy, a good test should also have reliability. It is an essential factor of an educational measurement. Generally it is difficult to obtain high reliability of an essay test. Essay test is often lack of accuracy and causes low reliability. Since it is not easy to have high reliability coefficient, the test item and the grading system must be designed in such a way  in order to improve the reliability coefficient. This article will look at the causes of low reliability, how to estimate and improve the reliability of an essay test.